The investment paradox: why attractive new ventures exhibit relatively poor investment potential. Issue 3 (3rd July 2017) - Cox, Kevin C.; Lortie, Jason; Gramm, Kimberly
Abstract: This paper provides insights into the way in which angel investors evaluate the investment potential of new ventures. Previous research has identified a broad array of different investment criteria that are thought to directly influence whether an investment opportunity is perceived as attractive by angel investors. This study contributes to this stream of research by identifying what is referred to as the investment paradox which occurs when the basic and fundamental investment criteria associated with a new venture are positively evaluated, yet the venture is simultaneously evaluated as exhibiting relatively poor investment potential. A model in which the relationship between fundamental investment criteria and overall investment potential is moderated by fit-based technology development criteria is proposed as an explanation for this apparent paradox. This model is tested with a large sample of investment proposals evaluated by angel investors using multi-level modeling. The results support the proposed moderated model of angel investor evaluation criteria. These results have clear and important implications for entrepreneurs, angel investors, public policy, and future research focused on angel investors' evaluations of investment opportunities.